Chart Smart: A Need for Documentation and Billing Education Among Emergency Medicine Residents? - Dawson, Brian (Department of Emergency Medicine, University of California, Irvine School of Medicine, 2010)
OBJECTIVE: The healthcare chart is becoming ever more complex, serving clinicians, patients, third party payers, regulators, and even medicolegal parties. The purpose of this study was to identify our emergency medicine (EM) resident and attending physicians’ current knowledge and attitudes about billing and documentation practices. We hypothesized that resident and attending physicians would identify billing and documentation as an area in which residents need further education. METHODS: We gave a 15-question Likert survey to resident and attending physicians regarding charting practices, knowledge of billing and documentation, and opinions regarding need for further education. RESULTS: We achieved a 100% response rate, with 47% (16/34) of resident physicians disagreeing or strongly disagreeing that they have adequate training in billing and documentation, while 91% (31/34) of residents and 95% (21/22) of attending physicians identified this skill as important to a resident’s future practice. Eighty-two percent (28/34) of resident physicians and 100% of attending physicians recommended further education for residents CONCLUSION: Residents in this academic EM department identified a need for further education in billing and documentation practices.